1995
DOI: 10.1017/s0033291700037521
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of eating disorders and minor psychiatric morbidity in Central Europe before the political changes in 1989: a cross-cultural study

Abstract: SYNOPSISThe prevalence of culture-bound syndromes such as eating disorders in the countries of Central and Eastern Europe is unclear and comparative epidemiological studies are lacking. Before the political changes in 1989 we therefore investigated eating disorders, eating attitudes and psychological health in two Eastern European countries and in one Western democracy. A total of 1225 female and male medical students in Hungary, the German Democratic Republic (GDR) and Austria were surveyed. The instruments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 28 publications
3
30
0
1
Order By: Relevance
“…29 This finding is in accordance with results from other studies that showed that Russian-speaking or former-Soviet bloc countries have slowly begun to adopt Western beauty norms. 19,20 Thus, the rate of acculturation or cultural change may be an important mediating variable in the trend toward disordered eating.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…29 This finding is in accordance with results from other studies that showed that Russian-speaking or former-Soviet bloc countries have slowly begun to adopt Western beauty norms. 19,20 Thus, the rate of acculturation or cultural change may be an important mediating variable in the trend toward disordered eating.…”
Section: Resultssupporting
confidence: 91%
“…It is impossible to compare this finding with other research, since the few studies that have been done on non-Western populations, [18][19][20] among which 29,30 Another possible explanation is that the BMI levels among new immigrant men and women are fairly similar, suggesting that weight gain and the efforts to control that weight gain are not an issue for either group.…”
Section: Resultsmentioning
confidence: 71%
“…A lower perfectionism in comparison to the Canadian samples was also reported for a Swedish sample (Norring & Sohlberg, 1988) and Japanese samples (Pike & Mizushima, 2005;Tachikawa et al, 2004). A comparison between Russian and British female students yielded higher scores for the Russian sample (O'Keefe & Lovell, 1999) which might be due to an over identification with Western ideals (see also Rathner et al, 1995). These results for the psychological dimensions of the EDI might again be due to differences in maturation.…”
Section: Discussionmentioning
confidence: 60%
“…Por seu lado, Kurth et al (1995), ao estudarem o comportamento alimentar de 1367 estudantes universitárias, concluíram que a prevalência da bulimia era de aproximadamente 2%. No mesmo ano Rathner et al (1995) verificaram que a taxa de prevalência para a bulimia nervosa nas mulheres na Hungria era de 1%, na Áustria, 0,6%, e na República Democrática da Alemanha, 0,0%. Para as situações sub clínicas de bulimia nas mulheres da Hungria havia 3,8% ao passo que na Áustria apenas 1,9% e na República Democrática da Alemanha 1,7% de casos relatados.…”
Section: Prevalência Das Doenças Do Comportamento Alimentar Tendo Preunclassified